PREDICtors for health-related quality of life after elective sigmoidectomy for DIVerticular disease: the PREDIC-DIV study protocol of a prospective multicentric transnational observational study - Sohn, Maximilian (BMJ Open, 2020)
INTRODUCTION: Diverticulitis is among the most common abdominal disorders. The best treatment strategy for this complicated disease as well as for recurrent stages is still under debate. Moreover, little knowledge exists regarding the effect of different therapeutic strategies on the health-related quality of life (HrQoL). Therefore, the PREDIC-DIV (PREDICtors for health-related quality of life after elective sigmoidectomy for DIVerticular disease) study aims to assess predictors of a change in HrQoL in patients after elective sigmoidectomy for diverticular disease. METHODS AND ANALYSIS: A prospective multicentre transnational observational study was started in November 2017. Patients undergoing elective sigmoid resection for diverticular disease were included. Primary outcome includes HrQoL 6 months postoperatively, staged by the Gastrointestinal Quality of Life Index (GIQLI). Secondary outcomes include HrQoL 6 months after sigmoidectomy, assessed using the Short Form 36 Questionnaire and a custom-made Visual Analogue Scale-based inventory; HrQoL after 12 and 24 months; postoperative morbidity; mortality; influence of surgical technique (conventional laparoscopic multiport operation vs robotic approach); histological grading of inflammation and morphological characteristics of the bowel wall in the resected specimen; postoperative functional changes (faecal incontinence, faecal urge, completeness of emptying, urinary incontinence, sexual function); disease-specific healthcare costs; and changes in economic productivity, measured by the iMTA Productivity Cost Questionnaire. The total follow-up will be 2 years. ETHICS AND DISSEMINATION: The protocol was approved by the medical ethical committee of the Bavarian Medical Council (report identification number: 2017-177). The study was conducted in accordance with the Declaration of Helsinki. The findings of this study will be submitted to a peer-reviewed journal (BMJ Open, Annals of Surgery, British Journal of Surgery, Diseases of the Colon and the Rectum). Abstracts will be submitted to relevant national and international conferences. TRIAL REGISTRATION NUMBER: The study is registered with the ClinicalTrials.gov register as NCT03527706; Pre-results.